Determination of methyl tetrahydrofolate reductase, TEAD2 and PAX3 gene polymorphisms in patients with spina bifida - Saraç, Mehmet; Özel, Şeyhmus Kerem; Önalan, Ebru Etem; Yüce, Hüseyin; Bakal, Ünal (Logos Medical Publishing, 2014)
Introduction: Several studies have evaluated the role of gene polymorhisms in etiopathogenesis of spina bifida (SB). The aim of this study is to evaluate methyl tetrahydrofolate reductase (MTHFR), Transcription factor2 (TEAD2) and Paired-Box3(PAX3) gene polymorphisms and allele frequencies in patients with SB in eastern part of Turkey. MTHFR activity plays a critical role in folate metabolism. PAX3 and TEAD2 are two different genes that are functional in closure of neural tube. Material and Methods: The study group included children with SB, children without any sacral anomalies, was accepted as the control group. MTHFR and TEAD2 were analised by “Polymorphisms Restriction Fragment Length Polymorphism” method and for PAX3 determination, “Polymorphism Amplification Specific Oligonucleotide” methods. Data were analysed using chi-square, Mann-Whitney U tests and Pearson's correlation analysis. Results: There were 67 patients with SB in the study group and 72 children in the control group. The mean age of chidren were 2.4 years and 7.8 years in the study and control group, respectively. In the study group, there were 65 meningomyelocele and 2 meningocele patients. In seven patients, SB was detected in another family member and 17 patients had consanguinity in family history. No significant difference was detected in MTHFR and TEAD2 gene polymorphisms between control and study groups. PAX3 gene polymorhism did not differ between controls and study group in genotype distribution. G allele was found to have an increased frequency in the study group (p=0.03). Conclusion: SB development depends on multifactorial mechanisms. Results show that TEAD2 and MTHFR gene polymorphisms, in contrary to other studies in the literature, may not contribute the formation of SB in our patient population. Our data indicate that PAX3 gene polymorphisms may be a contributing factor for the development of SB. More accurate determination of genetic backgrounds of SB may help to solve the development mechanisms of the disease. © Cocuk Cerrahisi Dergisi. All rights reserved.
Spina bifida hastalarında metilen tetrahidrofolat redüktaz, TEAD2 ve PAX3 gen polimorfizmlerinin araştırılması
Keywords: MTHFR; PAX3; Single nucleotide polymorphism; Spina bifida; TEAD2